Accounting Fraud Tendency on Village Credit Institution - I Gede Cahyadi Putra; Putu Wenny Saitri; I Gusti Bagus Ngurah Gunadi (AIBPM Publisher, 2019)
This study aims to examine the effect of suitability of compensation, information asymmetry, effectiveness of internal control, adherence to accounting rules, and the organization's ethical culture of accounting fraud. The research population of all village credit institution in Bangli is 159 with as many as 318 respondents. The results showed that information asymmetry had a positive effect, compliance with accounting rules had a negative effect, and conformity of compensation, effectiveness of internal controls and organizational ethics did not affect the tendency of accounting fraud. The results of the study show that information asymmetry is a factor causing fraud and this can be overcome by the obedience of accounting rules in the village credit institution. Keywords: fraud, accounting, village credit institutions